2018
DOI: 10.1002/14651858.cd000341.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fat supplementation of human milk for promoting growth in preterm infants

Abstract: Fat supplementation of human milk for promoting growth in preterm infants (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Most current evidence is based on limited studies with low to medium study quality [14][15][16]18,19,21]. A review assessing the effect of cup feeding versus other forms of supplemental enteral feeding, for infants unable to fully breastfeed, reported similar findings as observed in our review [11].…”
Section: This Review's Findings In Contextsupporting
confidence: 77%
See 1 more Smart Citation
“…Most current evidence is based on limited studies with low to medium study quality [14][15][16]18,19,21]. A review assessing the effect of cup feeding versus other forms of supplemental enteral feeding, for infants unable to fully breastfeed, reported similar findings as observed in our review [11].…”
Section: This Review's Findings In Contextsupporting
confidence: 77%
“…Many early-life interventions to improve growth among young infants have been tested, ranging from cup feeding to spoon-feeding to the fortification of either human/donor breastmilk or formula [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, currently, especially for infants who are already small or at-risk, there is insufficient data to develop recommendations [ 14 , 15 , 16 , 18 , 19 , 20 , 21 ]. In 2011 and 2013, WHO published recommendations on the feeding of LBW infants and management of severe acute malnutrition among infants <6 m, respectively; these recommendations were based on a limited and low or very low quality of evidence [ 8 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This metaanalysis was done on formula fed infants. Formula fed infants were excluded in our study.An earlier study showed no effect on short term growth of preterm infants fed fat supplemented human milk [20]. Our study also shows similar growth in all study groups over the study period of 2 months.…”
Section: Discussionsupporting
confidence: 83%
“…Only one study reported on the sources of funding for the studies (Q10). 26 All reviews except one 25 reported potential sources of conlfict of interest. The only review that was not a Cochrane review had several methodological flaws which led to a critically low level of confidence in its findings.…”
Section: Methodological Quality Of the Included Reviewsmentioning
confidence: 99%
“…The review included 1 study with only 14 babies; there was no evidence that the addition of fat improved in-hospital growth or affected tolerance of feeds. 25 The quality of evidence was very low due to Open access incomplete description of the methodology and small sample size. A review that assessed the effect of supplementation of human milk with short-chain galacto-oligosaccharides/ long-chain fructo-oligosaccharides included 1 study with 75 participants.…”
Section: How To Advance Enteral Feedsmentioning
confidence: 99%